Emerging economic scenario - Trivedi, I. V. (ed.) (Jaipur, 2004)
Economic development of a country has an important bearing on the structure of its economy. Several consequent upon economic development. All these changes indicate that India is coming out of the shackles of economic backwardness,yes it is an under developed economy. In the present volume efforts have been made by the learned contributor to analysed important Indian Capital Market reform in the light of on-going economic and financial sector reform measures.
Keywords: Economic development